The challenge of assigning groups - Frennesson, Lina; Lama, Phudoma; Libertson, Frans; Martin, Tina ; 0000-0002-1059-4514; Wahlström, Fanny (2020)
Group work is increasingly used in higher education and is associated with several benefits, both for the students and the teacher. How groups are assigned is of significance for the success of group work. This study aspires to explore the ways in which teachers can assign groups in order to enable successful group work. The findings indicate that heterogeneous groups that consist of students with complementary abilities are the most favourable for successful group work. Furthermore, three different methods for assigning groups were identified via interviews with teachers in higher education: 1) groups intentionally assigned by teacher, 2) randomly assigned by teacher, and 3) groups decided by students. Each method is however associated with both advantages and disadvantages, and it appears challenging for teachers to assign groups in an optimal manner.